Solar Energy Engineering: Processes and Systems - Kalogirou, Soteris A. (My University, 2023)
Solar Energy Engineering: Processes and Systems, Third Edition, includes updated chapters and extended resources to assist in the research and teaching of solar energy engineering. Sections cover advances in solar collectors, solar water heating, solar space heating and cooling, industrial process heat, solar desalination, photovoltaic technology, solar thermal power systems, modeling of solar energy systems, and a new chapter on wind energy systems. This book provides students, teachers and professionals with the basic principles and applications of solar energy systems and processes to help them understand how to operate and design solar systems. In addition, this best-selling title includes a student and academic companion site with additional materials on chapter PowerPoints for teaching, problems with a solutions manual, and equations files to assist in problem-solving.
Keywords: Electrical Engineering; Solar energy